Level of Awareness of Social Media Users on Cyber Security: Case Study among Students of University Tun Hussein Onn Malaysia - et. al., Shahidah Hamzah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The vast development of modern technology has resulted in a great impact on the life of children today and extended to teenagers group. This research was conducted to identify the level of awareness of university students on cybercrime. For this research purpose, the respondents involved were among the students of Universiti Tun Hussein Onn Malaysia, Pagoh campus. The total number of respondents that was targetted for this research was around 100 people. The instrument used was in quantitative form using questionnaire given to the respondents. The research outcome found that the level of university students’ awareness towards cyber security is at moderate level. Therefore, many proactive steps need to be implemented by the stakeholders so that issues that are relevant to cybercrime can be reduced and later be rid of.